Efficacy of vitamin D supplementation in major depression: A meta-analysis of randomized controlled trials - Vellekkatt, F; Menon, V (Journal of postgraduate medicine, 2019)
Background: There is a need to develop and periodically evaluate new treatment strategies in major depression due to the high burden of nonresponse and inadequate response to antidepressants. Aim: We aimed to assess the effect of vitamin D supplementation on depression symptom scores among individuals with clinically diagnosed major depression. Materials and Methods: Electronic search of databases was carried out for published randomized controlled trials in English language, peer-reviewed journals from inception till August 2017. Outcome measure used for effect size calculation was depression symptom scores. Effect sizes for the trials were computed using standardized mean difference (Cohen's d), and I2 test was used to assess sample heterogeneity. Pooled mean effect sizes were derived using both fixed and random-effects model. Critical appraisal of studies was done using the Cochrane risk of bias assessment tool. Results: A total of four trials involving 948 participants were included in the study. In three trials, the intervention group received oral vitamin D supplementation whereas in one parenteral vitamin D was given. Pooled mean effect size for vitamin D supplementation on depressive symptom ratings in major depression was 0.58 (95% confidence interval, 0.45-0.72). The I2 value for heterogeneity was 0 suggesting low heterogeneity among studies. Egger plot intercept indicated minimal publication bias. Conclusion: Vitamin D supplementation favorably impacted depression ratings in major depression with a moderate effect size. These findings must be considered tentative owing to the limited number of trials available and inherent methodological bias noted in few of them.